Absorption Of Agniveers & Moulding Them Into Better Citizens Col - Col Manjunath Raju; Dr. Smitha Viswanathan Girija (Educational Administration: Theory and Practice, 2024)
The Agnipath Scheme overhauls Indian Armed Forces hiring and management. The Indian government started it. This program recruits young Agniveers for four years. The purpose is to strengthen the country’s defense and increase it. Structured military training and exposure are intended to build discipline, resilience, leadership, and patriotism in these young recruits. Agniveers should be responsible, motivated, and civic-minded civilians following their service. While the Agnipath Scheme has lofty intentions, little is known about its long-term effects on society, particularly on civic and leadership abilities learned in short-term military service. This paper proposes a solid conceptual and quantitative framework for investigating Agniveers’ civic society integration to fill this gap. A thorough study of how this military training influences Agniveers’ leadership, intrinsic drive, and civic engagement is presented in the paper. It uses well-known principles concerning transformational leadership, motivation-hygiene dynamics, and social identity construction. This assessment is also crucial for policy, according to the essay. It also requires systematic post-service support to integrate Agniveers into the country’s economy and society. Future empirical research using the framework will enable policymakers, defense planners, and civil society groups maximize the Agnipath Scheme’s potential for change. This approach can make the country safer and make people more disciplined, skilled, and involved.